Pemberdayaan Mualaf Pasca Konversi di Dusun Tarangkin Kecamatan Peramasan Bawah - Muhammad Noor Wahidin; Muhammad Muttaqin; Cahaya Camelia; Heldawati Heldawati; Siti Aminah; Syifa Syifa; Saifuddin Ahmad Husin (UIN Antasari Banjarmasin, 2022)
AbstractThe converts in strengthening their religion need moral and social support. This is based on the commitment and consequences of post-conversion converts who are vulnerable to conflict and threats from within the family. Several studies that discuss the issue of converts are more focused on the process of religious conversion. Meanwhile, converts who receive threats from the family need special empowerment with the aim of giving the right to freedom of religion. Therefore, researchers will discuss the issue of post-conversion converts and the role of KKN students in fostering converts. This study uses a psychological approach to religion and the theory of religious empowerment. The research method used is descriptive-qualitative by observing more closely in life so that it is easier to follow the flow of life. Data collection includes participatory observation, interviews, questionnaires, and documentation. Data analysis was carried out using data reduction procedures, data presentation and data leveraging using triangulation methods, and drawing conclusions. The results of the study: 1) The converts received threats and severance of relations with their families after the creed. 2) Students provide moral assistance in assisting converts after the creed by assisting the process of religious stabilization after the creed.AbstrakPara mualaf dalam memantapkan keberagamaannya membutuhkan dukungan moral dan sosial. Hal ini berdasarkan komitmen dan konsekuensi mualaf pasca konversi yang rentan dengan konflik maupun ancaman dari pihak keluarga. Beberapa penelitian yang membahas isu mualaf lebih fokus dalam proses konversi agama. Sedangkan mualaf yang mendapatkan ancaman dari pihak keluarga membutuhkan pemberdayaan khusus dengan tujuan memberikan hak kebebasan beragama. Oleh karena itu, peneliti akan membahas problem mualaf pasca konversi dan peran Mahasiswa KKN dalam membina para mualaf. Penelitian ini menggunakan pendekatan psikologi agama dan teori pemberdayaan keagamaan. Metode penelitian yang digunakan yaitu deskriptif-kualitatif dengan mengamati lebih dekat dalam kehidupan informan sehingga lebih mudah untuk mengikuti alur kehidupannya. Pengumpulan data meliputi observasi partisipatif, wawancara, kuisioner, dan dokumentasi. Analisis data yang dilakukan dengan prosedur reduksi data, penyajian data serta verifikasi data menggunakan metode triangulasi, dan penarikan kesimpulan. Hasil penelitian menunjukkan: 1) Para mualaf mendapatkan ancaman dan pemutusan hubungan dengan keluarga pasca syahadat. 2) Mahasiswa memberikan bantuan moral dalam pendampingan mualaf pasca syahadat dengan tujuan membantu proses pemantapan beragama pasca syahadat.